2023
DOI: 10.3390/jfb14020089
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Treatments on Zirconia Bond Strength and Durability

Abstract: To evaluate the effects of airborne particle abrasion (APA) combined with MDP-containing resin cement, a glass-ceramic spray deposition (GCSD) method on the shear bond strengths (SBSs) and durability of 3 mol% yttrium oxide-stabilized zirconia ceramic (3Y-TZP) compared with lithium disilicate glass ceramics (LDGC). 3Y-TZP disks were randomly treated as follows: for Group APA+MDP, 3Y-TZP was abrased using 50 μm Al2O3 particles under 0.1 Mpa and bonded with MDP-containing resin cement; for Group GCSD, 3Y-TZP was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Similar differences between sandblasted samples and those additionally etched with a strong acid solutions were also observed in other studies [12,23,24]. Proper surface treatments may promote the micromechanical interlocking of resin cement by creating fitting roughness and increasing surface energy [11,[25][26][27]. Profilometers are commonly used to characterize roughness.…”
Section: Discussionsupporting
confidence: 72%
“…Similar differences between sandblasted samples and those additionally etched with a strong acid solutions were also observed in other studies [12,23,24]. Proper surface treatments may promote the micromechanical interlocking of resin cement by creating fitting roughness and increasing surface energy [11,[25][26][27]. Profilometers are commonly used to characterize roughness.…”
Section: Discussionsupporting
confidence: 72%
“…An examination of these works revealed that 3 papers (10%) utilized experimental methodology, 6 papers (21%) discussed the reported results and compared them with their findings, and 20 papers (69%) cited 1 or more of Dr. Santos’s papers in the introduction section of their papers to explain a concept (Table S1 in the Supporting Information). More details and discussion about these relevant studies ,, are available in the Supporting Information file alongside other analyses on citation usage, publication sources, country, institutional collaboration analyses, and paper classification according to scientific disciplines and the United Nations Sustainable Development Goals. A scientometric analysis is a powerful tool for researchers to gauge the impact of their work and to connect with the broader scientific community beyond what other networking activities, such as conferences and webinars, allow.…”
Section: Scientometric Analysismentioning
confidence: 99%
“…With 5% HF inscription for 90-120 seconds at a pressure of 0.3 Mpa, a new glass ceramic spray deposition (GCSD) approach has recently been described to increase the zirconia bond strength. It is possible to create an extremely thin layer that does not alter the zirconia's physical characteristics by spraying glass-ceramic powders over zirconia surfaces which are subsequently sintered [52].…”
Section: Zirconia Treatmentsmentioning
confidence: 99%